Teneurins: Mediators of Complex Neural Circuit Assembly in Mammals - Leamey, Catherine A.; Sawatari, Atomu (Frontiers in Neuroscience, 2019)
The teneurins (Ten-m/Odz) are a family of evolutionarily ancient transmembrane molecules whose complex and multi-faceted roles in the generation of mammalian neural circuits are only beginning to be appreciated. In mammals there are four family members (Ten-m1-4). Initial expression studies in vertebrates revealed intriguing expression patterns in interconnected populations of neurons. These observations, together with biochemical and over-expression studies, led to the hypothesis that homophilic interactions between teneurins on afferent and target cells may help to guide the assembly of neural circuits. This review will focus on insights gained on teneurin function in vivo in mammals using mouse knockout studies. These studies provide support for the hypothesis that homophilic interactions between teneurin molecules can guide the formation of neural connections with largely consistent results obtained in hippocampal and striatal circuits. Mapping changes obtained in the visual pathway, however, suggest additional roles for these glycoproteins in the formation and specification of circuits which subserve binocular vision.